Prevalence, self-awareness, and LDL cholesterol levels among patients highly suspected as familial hypercholesterolemia in a Japanese community - Hayato Tada; Junichi Shibayama; Tetsuo Nishikawa; Hirofumi Okada; Akihiro Nomura; Soichiro Usui; Kenji Sakata; Atsushi Hashiba; Akihiro Inazu; Masayuki Takamura; Masa-aki Kawashiri (Practical Laboratory Medicine, 2020)
Backgrounds: The prevalence of familial hypercholesterolemia (FH) among Japanese populations is still unclear. In addition, no prior data exist regarding the self-awareness. Accordingly, we aimed to investigate the prevalence, self-awareness, and LDL-C of patients with highly suspected as FH using data obtained in a community-based medical checkups. Methods: This study included 52,276 subjects (18,588 men, 35.6%) aged ≥40 years who underwent the Japanese specific health checkup in Kanazawa City during 2018. We assessed the self-awareness of dyslipidemia (and the age) as well as the prevalence of patients with highly suspected as FH whose naïve LDL-C levels were ≥250 ​mg/dl. Naïve LDL-C levels were estimated by the adjustment (LDL-C/0.7) for those on lipid-lowering medication. We divided subjects into 3 groups based on their naïve LDL cholesterol level (≥250 ​mg/dl, 140–249, and ≤139 ​mg/dl). Results: We identified 262 (0.5%) individuals highly suspected as FH whose naïve LDL-C levels were ≥250 ​mg/dl. Most of them (234 among 262, 89%) were under lipid-lowering medication; however, the self-awareness as dyslipidemia was not quite high (200 among 262, 76%), and their mean LDL-C level under lipid-lowering medication was 203 ​± ​35 ​mg/dl. Interestingly, the age of acknowledgement of dyslipidemia among the patients with highly suspected as FH was significantly younger than those in other categories (58 vs. 60/62 ​yrs, respectively, p ​< ​0.05 for both). Conclusions: The prevalence of patients highly suspected as FH was around 1 in 200, and their self-awareness as well as control were not still good enough among Japanese general populations.